Equilibrium isotherm modeling, kinetics and thermodynamics study for removal of lead from waste water - Chowdhury, Z.Z.; Rashid, A.K.; Zain, Sharifuddin Md (2011)
The low cost adsorbent palm oil fuel ash (POFA) derived from an agricultural waste material was investigated as a replacement of current expensive methods for treating wastewater contaminated by Pb(II) cation. Adsorption studies were carried out to delineate the effect of contact time, temperature, pH and initial metal ion concentration. The experimental data followed pseudo second order kinetics which confirms chemisorptions. The values of Langmuir dimensionless constant, R(L) and Freundlich constant, 1/n were less than 1 representing favorable process for adsorption. Thermodynamic parameters such as Delta G degrees, Delta H degrees and Delta S degrees, related to Gibbs free energy, enthalpy and entropy were evaluated. It was concluded that, chemically treated palm oil fuel ash (POFA) can be used successfully for adsorption of Pb(II) from aqueous solution.